Heart remodeling produced by aortic stenosis promotes cardiomyocyte apoptosis mediated by collagen V imbalance. Issue 4 (December 2018) - Sant'Ana, Paula Grippa; Batah, Sabrina Setembre; Leão, Patrícia Santos; Teodoro, Walcy Rosolia; de Souza, Sérgio Luiz Borges; Ferreira Mota, Gustavo Augusto; Vileigas, Danielle Fernandes; da Silva, Vitor Loureiro; de Campos, Dijon Henrique Salomé; Okoshi, Katashi; Capelozzi, Vera Luiza; Cicogna, Antonio Carlos; et al.
Abstract: Cardiac remodeling (CR) is a structural change of the heart due to chronic hemodynamic overload related to changes in both myocyte and extracellular matrix (ECM). We investigated that the imbalance of collagen V promotes cardiomyocyte apoptosis that contributes to heart failure and cell death. Aortic stenosis was induced surgically and male Wistar rats were randomized to 18 weeks (Sham 18 w, n = 12; AoS 18 w, n = 12) and severe of heart failure (Sham HF, n = 12; AoS HF, n = 12) groups. Functional and structural echocardiogram, immunohistochemistry for Ki-67, TUNEL assay and Immunofluorescence for collagen were performed. Our main results were:( 1) Progressive reduction of cardiac functional capacity due to cardiac remodeling with decreased eject fraction in heart failure; (2) Imbalance of collagen deposition with increased, crowded and irregular collagen I in situ expression; (3) Dysregulation of dynamic control of collagen fibers with exposed epitopes of collagen V; (4) Additional apoptosis that are dependent to cardiac injury. The collagen V expression in cardiac remodeling is for the first time described and may be related to additional apoptosis and autoimmune response. Our findings suggest a critical role of collagen V in cardiac remodeling to modulate and promote heart failure and death.